Resolusi Konflik Sosial Keagamaan Di Kota Bandung - Zulfiqri Sonis Rahmana (UIN Sunan Gunung Djati Bandung, 2018)
Religion must be a source of social order and inner peace as something that glamorize and glorify, and make a civilized man. Implementation of religious teachings should be a guideline for human life in order to achieve happiness together. However, in doing social life of human society faced with three problems, namely inability, powerlessness and uncertainty. So today, especially in Bandung, often socio-religious conflict played by the followers of the religion itself. Ironically, the religious teachings of the estuary is often seen as a conflict. This is the dissonance between theory and facts, causing a mismatch. Thus, the researchers want to analyze to these problems, by focusing research on socio-religious conflict resolution in Bandung, whether the function of religion as a cause of conflict or even as conflict resolution.